Selective Inhibition of the Immunoproteasome β5i Prevents PTEN Degradation and Attenuates Cardiac Hypertrophy - Xie, Xin; Wang, Hong-Xia; Li, Nan; Deng, Ya-Wen; Bi, Hai-Lian; Zhang, Yun-Long; Xia, Yun-Long; Li, Hui-Hua (Frontiers in Pharmacology, 2020)
Cardiac hypertrophy without appropriate treatment eventually progresses to heart failure. Our recent data demonstrated that the immunoproteasome subunit β5i promotes cardiac hypertrophy. However, whether β5i is a promising therapeutic target for treating hypertrophic remodeling remains unknown. Here we investigated the effects of PR-957, a β5i-specific inhibitor, on angiotensin II (Ang II)–induced hypertrophic remodeling in the murine heart. The infusion of Ang II increased immunoproteasome chymotrypsin-like activity and β5i catalytic subunit expression in the heart, whereas PR-957 treatment fully blocked the enhanced immunoproteasome activity caused by Ang II. Moreover, the administration of PR-957 significantly suppressed Ang II–induced cardiac hypertrophy, fibrosis, and inflammation. Mechanistically, PR-957 treatment inhibited phosphatase and tensin homologue on chromosome ten (PTEN) degradation, thereby inhibiting multiple signals including AKT/mTOR, ERK1/2, transforming growth factor-β, and IKB/NF-kB. Furthermore, PTEN blocking by its specific inhibitor VO-OHpic markedly attenuated the inhibitory effect of PR-957 on Ang II–induced cardiac hypertrophy in mice. We conclude that PR-957 blocks PTEN degradation and activates its downstream mediators, thereby attenuating Ang II–induced cardiac hypertrophy. These findings highlight that PR-957 may be a potential therapeutic agent for Ang II-induced hypertrophic remodeling.